Adaptive potential of winter rye cultivars developed at VIR in the context of their grain protein content in the environments of Leningrad province - N. I. Aniskov; I. V. Safonova; V. I. Horeva (Труды по прикладной ботанике, генетике и селекции)
Background. In Leningrad Province, winter rye is an irreplaceable cereal crop for food and feed. At present, a reduction of the acreage under rye is observed. This situation may be changed by developing rye cultivars capable of maintaining high and stable protein content across variable natural environments.The objective of the research encompassed 9 winter rye cultivars developed by V. D. Kobylyansky and O. V. Solodukhina at VIR, all recommended for cultivation in this area.Materials and methods. The experimental part of the work was carried out in 2012–2017 in the fields of Pushkin and Pavlovsk Laboratories of VIR. Nine low-pentosan winter rye cultivars bred at VIR were analyzed. Sowing time was within the period from August 28 to September 11. Agricultural practice used in the experiments was conventional for the Northwestern Region. The area of the plot was 10 m2; there were three replications. Seeding rate was 350 seeds/m2 or 3.5 million viable seeds per hectare. Analysis of variance was used for mathematical processing. Parameters of adaptability, stability, plasticity and stress resistance were calculated for the “grain protein content” indicator.Results. Protein content in grain for the studied winter rye cultivars in the environments of the Northwest region averaged 10.3% and varied from 8.7% to 12.2% depending on environmental conditions and hereditary features of the cultivars. It was confirmed by the results of the analysis of variance: the share of the ‘year of trial’ factor’s effect on protein content was 71.9%. The best conditions for increased protein content were observed in 2012, 2013 and 2016 (10.7%, 11.9% and 12.2%, respectively). The analysis of average protein content in grain showed that the cultivars ‘Ilmen’, ‘Vavilovskaya’, ‘Krasnoyarskaya universalnaya’, Novaya Era, ‘Yantarnaya’ exceeded the reference cultivar ‘Era’ by (1.0 – 10.0%). The most adaptable in the context of grain protein content under the conditions of the Northwestern Region were the winter rye cultivars ‘Ilmen’, ‘Era’, ‘Yantarnaya’, Novaya Era, and Rushnik 2. The sum of their ranks according to the coefficients of variation (V), environmental plasticity (O), relative trait stability (St²) and homeostasis (Hom), as well as each cultivar’s adaptability coefficient (AC), stress resistance level (Y min – Y max) and compensatory ability (Y min + Y max/2), was 13–31 units.Conclusion. Rye cultivars ‘Ilmen’, ‘Era’, ‘Yantarnaya’, Novaya Era, and Rushnik 2 possess high adaptability and can maintain high protein content levels in grain under widely varied environmental conditions in the Northwestern Region of Russia.